Kopolimerisasi Grafting Campuran N-Isopropilakrilamida dan Glisidil Metakrilat pada Film Polietilen yang Diinduksi oleh Sinar Ultraviolet - Suka, Irwan Ginting (Jurnal Natur Indonesia, 2008)
Liquid phase ultraviolet irradiation was used to graft the mixtures of N-isopropylacrylamide and glycidyl methacrylateto a linear low-density polyethylene film (thickness of 30 μm) surface. Xanthone was used as photoinitiator, whichwas coated on the film surface earlier. The surface of the grafted polyethylene samples were characterized byattenuated total-reflection IR spectroscopy and scanning electron microscopy. Elemental analysis indicated thatthe NIPAAm fraction with respect to GMA in the graft copolymer increased with increasing NIPAAm ratio in thecomonomer feed solution. The reactivity ratios of NIPAAm and GMA monomers determined in the present graftcopolymerization system were found to be 0,31 ± 0,1 and 4,8 ± 0,2, respectively. It was found that the epoxy groupsof GMA-grafted chains in the NIPAAm/GMA-grafted films have the ability to react with ethylenediamine (En). Theaminated NIPAAm/GMA-grafted film had an excellent ability to adsorb cupric ion. The temperature-responsivecharacter of the resulting grafted films was evaluated by measuring the water absorbency of the grafted NIPAAm/GMA when immersed in water and/or methanol at 5 to 50 0C.